Developing Students’ Literacy and Communication Skills: A Fundamental Need for Enhancing Career Readiness - Rina Heryani; Melda Fauzia Damaiyanti; Rini Utari (Aksara, 2026)
Effective communication is a core competency required for university students to achieve academic success and workplace readiness. This study aims to examine students’ perceptions of the importance of communication skills, the frequency with which they are applied in real academic contexts, and the priority dimensions of speaking skills considered essential. A qualitative approach was employed, and data were collected through open-ended and structured questionnaires administered to 54 respondents from diverse study programs. Data were analyzed using thematic analysis following Miles, Huberman, and Saldana, involving data reduction, data display, and conclusion drawing/verification. The analysis process included coding responses, categorizing emerging patterns, and synthesizing themes interpretively to ensure analytical rigor and trustworthiness. The findings indicate that although students demonstrate a high level of awareness regarding the importance of communication, the frequency of its application in daily academic activities remains relatively low. Moreover, communication skills were found to contribute to students’ confidence, critical thinking, and writing abilities, reinforcing their role as integral components of academic literacy. The study recommends that higher education institutions integrate communication skills into the curriculum to foster functional literacy and enhance students’ career readiness in a comprehensive and holistic manner. AbstrakKomunikasi yang efektif merupakan kompetensi inti yang diperlukan mahasiswa untuk mencapai keberhasilan akademik dan kesiapan memasuki dunia kerja. Penelitian ini bertujuan untuk mengkaji persepsi mahasiswa terhadap pentingnya keterampilan komunikasi, frekuensi penerapannya dalam konteks akademik nyata, serta dimensi prioritas keterampilan berbicara yang dianggap esensial. Penelitian ini menggunakan pendekatan kualitatif dengan pengumpulan data melalui kuesioner terbuka dan terstruktur yang diberikan kepada 54 responden dari berbagai program studi. Data dianalisis menggunakan analisis tematik mengacu pada Miles, Huberman, and Saldana yang meliputi reduksi data, penyajian data, serta penarikan dan verifikasi kesimpulan. Proses analisis mencakup pengodean data, pengelompokan pola yang muncul, serta sintesis tema secara interpretatif untuk menjamin ketelitian analitis dan keabsahan temuan. Hasil penelitian menunjukkan bahwa meskipun mahasiswa memiliki tingkat kesadaran yang tinggi terhadap pentingnya komunikasi, frekuensi penerapannya dalam aktivitas akademik sehari-hari masih tergolong rendah. Selain itu, keterampilan komunikasi terbukti berkontribusi terhadap peningkatan kepercayaan diri, kemampuan berpikir kritis, dan keterampilan menulis mahasiswa sehingga menegaskan perannya sebagai komponen integral dalam literasi akademik. Penelitian ini merekomendasikan agar institusi pendidikan tinggi mengintegrasikan keterampilan komunikasi ke dalam kurikulum guna mengembangkan literasi fungsional serta meningkatkan kesiapan karier mahasiswa secara komprehensif dan holistik.